PEDAGOGICAL TECHNOLOGIES OF IMPLEMENTING THE INNOVATIVE KNOWLEDGE ACQUIRED IN PROFESSIONAL DEVELOPMENT AND PROFESSIONAL ADVANCEMENT COURSES OF TEACHERS IN PRACTICE - Sattorova Dilshoda Djavlievna (Scholar Express Journal, 2023)
In this article, the formation of the qualities of primary school teachers, such as the desire for pedagogical creativity, knowledge and research, the use of interactive methods, and their innovative activity, is a direct product of the educational process, in which the educational process in general secondary educational institutions is of great importance, which currently meets the world's requirements. creation, organization and wide use of innovative supplies that enable the training of competitive young people, organization of the educational process in general education schools by the pedagogical staff on the basis of innovative technologies and interactive methods is explained
Keywords: Creativity; technology; knowledge